1998
DOI: 10.1109/10.725330
|View full text |Cite
|
Sign up to set email alerts
|

Toward prediction of physiological state signals in sleep apnea

Abstract: A recurrent connectionist model is described to predict dynamic respiratory state in the apneic sleeping patient. The time-domain model of nonlinear time-lagged interactions between heart rate, respiration, and oxygen saturation was developed to implicitly embed the dynamics of the respiration and cardiovascular control systems. Multiple future time scales were enforced on the network during training to explore the limits of the prediction horizon and produce a global representation of dynamic state trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
0
26
0
3
Order By: Relevance
“…However, a small number of nonlinear dimensional analyses of respiration have been reported previously. BOCK et al [20] reported that, by analysing the largest Lyapunov exponent and correlation dimension, the respiratory state in sleeping patients with apnoea could be shown to have chaotic dynamics. The current authors have previously shown that respiratory movement in patients with severe OSAHS during apneoic sleep was random, as no D2 for respiratory movement during sleep with apnoea could be obtained [13].…”
Section: Analysis Of the Dimensionality For Respiratory Movementmentioning
confidence: 99%
“…However, a small number of nonlinear dimensional analyses of respiration have been reported previously. BOCK et al [20] reported that, by analysing the largest Lyapunov exponent and correlation dimension, the respiratory state in sleeping patients with apnoea could be shown to have chaotic dynamics. The current authors have previously shown that respiratory movement in patients with severe OSAHS during apneoic sleep was random, as no D2 for respiratory movement during sleep with apnoea could be obtained [13].…”
Section: Analysis Of the Dimensionality For Respiratory Movementmentioning
confidence: 99%
“…When the total lengths of the apnea and hypopnea periods are calculated, the consecutive and events must be joined, respectively. Many authors have pointed out the nonlinearity of cardio-respiratory signals [17], and used different types of artificial neural networks (ANNs) for their processing [18], [19]. We propose four different ANNs for time-domain respiration pattern classification.…”
Section: B Design Considerationsmentioning
confidence: 99%
“…The apneas in sleep can be classified into three types: 1) obstructive apnea, where the pharynx becomes occluded and eventually collapses; 2) central apnea, caused by fluctuations in central respiratory control; and 3) mixed disturbances, where aspects of both obstructive and central apneas are present (Silage 1990;Bock et al, 1998). In particular, the major cause of the OSA symptom (Behbehani et al, 1995;Yen et al , 1997;Favre et al, 2003;Tsai et al, 2008) is that a patient's airflow ceases because the pharyngeal wall collapses in sleep.…”
Section: Introductionmentioning
confidence: 97%
“…To diagnose OSA or other apneas, researchers have employed polysomnographic recordings that may include electrocardiogram, electroencephalogram, electrooculogram, or electromyogram measures of respiration, and arterial oxygen saturation (Bock and Gough, 1998). However, such recordings are always Downloaded by [The University of Manchester Library] at 05:20 09 October 2014 time-consuming.…”
Section: Introductionmentioning
confidence: 99%